Massificação e burocracia: gênese do totalitarismo à luz do pensamento arendtiano - Costa, Thainá Junges (Universidade do Vale do Rio dos Sinos, 2025)
Hannah Arendt, a German political philosopher of Jewish descent, experienced the rise of Nazism and analyzed phenomena such as massification and bureaucracy-tools used by certain politicians to dismantle traditional social and political structures, paving the way for the imposition of totalitarian ideologies. Given this context, this study poses the following research question: How do social massification and bureaucracy produce and sustain totalitarianism? To address this issue, a bibliographic methodology will be employed, drawing on articles and works related to the topic, primarily Hannah Arendt’s writings, especially The Origins of Totalitarianism (2012), Eichmann in Jerusalem: a Report on the Banality of Evil (1999), and The Human Condition (2007). This topic is considered relevant as it seeks to understand past political and social issues that remain pertinent today. Additionally, the study aims to explore how massification occurs, how bureaucracy can become dangerous, how both together lead to an alienated society, the role of propaganda in totalitarian politics, and the point at which prejudice ceases to be merely a negative social pattern and becomes a state weapon.
Keywords: Massificação; Burocracia; Totalitarismo; Hannah Arendt; Ideologia; Massification; Bureaucracy; Totalitarianism; Ideology; ACCNPQ::Ciências Humanas::Filosofia